Helping behaviour of volunteers in providing post-disaster psychosocial assistance - Nevi K. Arianti; Muhammad Baiquni; Koentjoro Soeparno; Arifin Nur A. I. (Jàmbá)
This study explores the ways that volunteers help in overcoming the negative impacts of disasters. The direction of this research is the production of guiding data for roadmaps for strengthening the capacity of volunteers as the spearhead of disaster risk reduction. The purpose of the study was to find out how the volunteers’ helping behaviour provides post-disaster psychosocial support. Two kinds of studies (multimethod) were conducted to answer the research questions. Study 1 was conducted on three volunteer participants, using the phenomenological method. Analysis of research data using interpretative phenomenological analysis. Study 2 was conducted on 69 volunteer respondents, using a survey method with open-ended questions to determine respondents’ perceptions of the meaning of helping and the meaning of psychosocial support. The results of data integration found five themes in helping behaviour which included the values of volunteers and their goals, motivation and attitudes in helping, cooperation with other parties, as well as special themes/other findings in the form of mottos owned by volunteers.